Algebraische Zahlentheorie: 14.8. bis 20.8.1977 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1977)
S. Agau, Lyon; H.-J. Bartels, Göttingen; S. A. Basarab, Bukarest; E. Becker, Köln; P. Báyer, Barcelona; H. Benz, Köln; C. J. Bushnell, London; D. G. Cantor, Los Angeles; H. Cohn, New York; R. W. Davis, San Diego; P. Draxl, Bielefeld; G. Frey, Saarbrücken; A. Fröhlich, London; W.-D. Geyer, Erlangen; B. Gordon, Los Angeles; F. Halter-Koch, Essen; H. Hasse, Hamburg; H. Hazewinkel, Rotterdam; F.-P. Heider, Köln; W. Henn, Karlsruhe; G. M. Ikeda, Ankara; M. Jarden, Tel-Aviv; W. Jehne, Köln; E. Kani, Heidelberg; H. I. Karakas, Heidelberg; K. Kiyek, Paderborn; N. Klingen, Köln; S. V. Kotov, Minsk; R. Lakkis, Thessaloniki; H. Lang, Münster; H. W. Lenstra, Amsterdam; A. Leutbecher, München; P. A. Loeb, Urbana; F. Lorenz, Münster; M. L. Madan, Columbus; G. Martens, Erlangen; B. H. Matzat, Karlsruhe; E. Maus, Göttingen; C. Meyer, Köln; M. Neubrand, Bonn; G. Poitou, Orsay; A. Prestel, Konstanz; J. Ritter, Berlin; P. Roquette, Heidelberg; W. Scharlau, Münster; R. Schertz, Köln; A. Schinzel, Warschau; V. Schulze, Berlin; V. Sprindzuk, Minsk; H.-J. Stender, Köln; R. J. Stroeker, Rotterdam; H. Stützer, Köln; O. Taussky-Todd, Pasadena; W. Trinks, Karlsruhe; J. Neukirch, Regensburg; Ch. J. Parry, Blacksburg; R. Perlis, Bonn; M. Pohst, Köln; R. W. van der Waall, Nymegen; C. D. Walter, Dublin; G. Wicke, Münster; H. G. Zimmer, Saarbrücken
Beitr. teilw. dt., teilw. engl
Keywords: Konferenzschrift